Anti-smuggling penal olicies: a cross-national exploration - Brandariz García, José Ángel (The challenges of illegal trafficking in the Mediterranean Area, 2023)
Human smuggling crimes and facilitation criminal offences have been widely explored by legal scholars. The legal literature has insightfully pointed out the various shortcomings of the legal provisions criminalising facilitation activities, contrasting them with the principles of a rights-based model of criminal justice. Much less research has been conducted on the actual enforcement of these criminal law provisions on the ground. This research gap is especially noteworthy with regard to comparative studies. This chapter contributes to bridge that gap by considering the various pitfalls stemming from the implementation of anti-smuggling penal policies in a number of western European countries. In so doing, the chapter explores the relative insignificance of smuggling and facilitation crimes in various jurisdictions, as well as their uneasy coexistence with irregular migration criminal offences. In addition, the chapter spotlights the effectiveness dimension of these penal policies, scrutinising what the rare enforcement of smuggling and facilitation crimes tells us about the role played by the criminal justice system in the coercive management of irregular migration.